Point Mutations as Main Resistance Mechanism Together With P450-Based Metabolism Confer Broad Resistance to Different ALS-Inhibiting Herbicides in Glebionis coronaria From Tunisia - Hada, Zeineb; Menchari, Yosra; Rojano-Delgado, Antonia M.; Torra, Joel; Menéndez, Julio; Palma-Bautista, Candelario; de Prado, Rafael; Souissi, Thouraya (Frontiers in Plant Science, 2021)
Resistance to acetolactate synthase (ALS) inhibiting herbicides has recently been reported in Glebionis coronaria from wheat fields in northern Tunisia, where the weed is wide-spreading. However, potential resistance mechanisms conferring resistance in these populations are unknown. The aim of this research was to study target-site resistance (TSR) and non-target-site resistance (NTSR) mechanisms present in two putative resistant (R) populations. Dose-response experiments, ALS enzyme activity assays, ALS gene sequencing, absorption and translocation experiments with radiolabeled herbicides, and metabolism experiments were carried out for this purpose. Whole plant trials confirmed high resistance levels to tribenuron and cross-resistance to florasulam and imazamox. ALS enzyme activity further confirmed cross-resistance to these three herbicides and also to bispyribac,but not to flucarbazone. Sequence analysis revealed the presence of amino-acid substitutions in positions 197, 376 and 574 of the target enzyme. Among the NTSR mechanisms investigated, absorption or translocation did not contribute to resistance, while evidences of the presence of enhanced metabolism were provided. A pretreatment with the cytochrome P450 monooxygenase (P450) inhibitor malathion partially synergized with imazamox in post-emergence but not with tribenuron in dose response experiments. Additionally, imazamox-OH metabolite was detected in both R populations in metabolism experiments, which disappeared with the pretreatment with malathion. This study confirms the evolution of cross resistance to ALS inhibiting herbicides in G. coronaria from Tunisia through TSR and NTSR mechanisms. The presence of enhanced metabolism involving P450 is threatening the chemical management of this weed in Tunisian wheat fields, since it might confer cross resistance to other sites of action.